Public Practices and Personal Perspectives - Kaebnick, Gregory E. (The Hastings Center report, 2017)
I once heard John Arras, who was one of bioethics’ bright lights and, toward the end of his life, a member of the Presidential Commission for the Study of Bioethical Issues, remark that it is hard for an ethics commission not to “do paint-by-numbers ethics.” What I think Arras had in mind is an approach that, in the set of essays that make up this special report, Rebecca Dresser describes as a listing of “general, often relatively uncontroversial” moral positions to support largely procedural recommendations. Arras was calling attention to one of the challenges and sometimes frustrations of commission thinking. It is a recurring topic in this special report, Goals and Practices of Public Bioethics, which features a series of reflections about how national bioethics commissions around the world have contributed to public understanding and public policy about bioethical issues. Both the topic and the authors are drawn from the final two public meetings of the PCSBI, which was the most recent U.S. example of a national bioethics commission and whose winding down created an occasion for pondering the different forms and functions of bioethics commissions.